AI Integration in Screening and Selection: The Impact of Perception of Fairness, Trust, and Usability in the Acceptability of HR Employees in Metro Manila - Marco, Frances Jezreel; Agngarayngay, Caryle; Tan, Charles Emmanuel; Latifi, Sasan Iman; Villamor-Evangelista, Mary Grace (The Institute of Academic Research and Publication (IARP), 2026)
The study examined how perceptions of fairness, trust, and usability predicted the acceptance of artificial intelligence integration in the screening and selection process. Researchers administered a cross‑sectional survey to 140 human resource professionals in Metro Manila who possessed experience using artificial intelligence in screening and selection. Multiple linear regression and partial least squares structural equation modeling were employed to develop the emerging structural model and obtain standardized coefficients. Findings revealed that usability significantly predicted acceptability, while trust predicted it to a slightly weaker extent. Fairness did not retain significance when it was entered alongside the other predictors. These findings suggested that human resource employees prioritized user-friendly and trustworthy artificial intelligence, which is critical for successful integration. The results highlighted the need for transparency, training, and support within the human resources department to better prepare staff for fostering ethical and effective integration of artificial intelligence in the workplace.